History in the Making: Establishing an Institutional Archive at The College of The Bahamas: - Seymour, Antoinette (International Journal of Bahamian Studies, 2015)
As the College of The Bahamas transitions to a university, an institutional archive housing records of legal, administrative, financial, educational, cultural, and historical significance has been formally established. The COB Institutional Archive will collect and preserve records and documents deemed to have permanent value, thereby making them accessible for future researchers. The archive, presently located in the Harry C. Moore Library Special Collections area, will include not only institutional records, manuscripts and documents but also College catalogues and other published ephemera.